1996
DOI: 10.1093/oxfordjournals.eurheartj.a015074
|View full text |Cite
|
Sign up to set email alerts
|

Mode of death in chronic heart failure: A request and proposition for more accurate classification

Abstract: The proportion of patients reported to die suddenly or from progressive circulatory failure is not consistent among studies of heart failure. Lack of an adequate or consistent classification of how patients die contributes to the current confusion over the mode of death in heart failure. Defining how patients with heart failure die could be important in developing strategies to reduce the continuing high mortality associated with this condition. We identified 27 studies that reported 50 or more deaths among pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
87
0
7

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(94 citation statements)
references
References 35 publications
0
87
0
7
Order By: Relevance
“…Although the proportion of sudden deaths in published trials varies significantly, probably due to varying interpretations of reported modes of death, clinical trials data suggests that SCD accounts for approximately one-third of all HF deaths [4]. Epidemiologic evidence from the Framingham heart study suggests that about one-half of all deaths due to HF occur within 1 h NIH Public Access…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the proportion of sudden deaths in published trials varies significantly, probably due to varying interpretations of reported modes of death, clinical trials data suggests that SCD accounts for approximately one-third of all HF deaths [4]. Epidemiologic evidence from the Framingham heart study suggests that about one-half of all deaths due to HF occur within 1 h NIH Public Access…”
Section: Introductionmentioning
confidence: 99%
“…Prior to advent of neuro-hormonal antagonists, the mean duration of survival after onset of HF was 1.7 years for men and 3.2 years for women, with only half of patients still alive after 5 years of onset [2]. The two modes of death in patients with HF are circulatory failure due to progressive left ventricular (LV) dysfunction associated with gradual worsening of symptoms, or sudden cardiac death (SCD) in relatively clinically stable patients [3].Although the proportion of sudden deaths in published trials varies significantly, probably due to varying interpretations of reported modes of death, clinical trials data suggests that SCD accounts for approximately one-third of all HF deaths [4]. Epidemiologic evidence from the Framingham heart study suggests that about one-half of all deaths due to HF occur within 1 h NIH Public Access…”
mentioning
confidence: 99%
“…In this patient population the most common causes of death include SCA and progressive heart failure 40. Yet, patients with more severe heart failure are more likely to die of progressive heart failure.…”
Section: Prognosis Of Patients After Icd Implantation For Secondary Pmentioning
confidence: 99%
“…Loss of myocardium secondary to recurrent myocardial infarction could lead to hospital admission, worsening heart failure and eventually death. Coronary occlusion could also be the leading cause of sudden cardiac death in heart failure [6]. Even among patients with docuffil~nted arrhythmic death coronary occlusion may play an important role [6].…”
Section: Introductionmentioning
confidence: 99%
“…Coronary occlusion could also be the leading cause of sudden cardiac death in heart failure [6]. Even among patients with docuffil~nted arrhythmic death coronary occlusion may play an important role [6]. Anti-thrombotic treatment could also reduce the risk of overt or occult cerebral thrombo-embolism [5,7,8] and other pulmonary or peripheral embolic phenomena that could contribute to morbidity and mortality in heart failure.…”
Section: Introductionmentioning
confidence: 99%